2005
DOI: 10.1038/sj.jp.7211277
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal and Infant Mortality in the Ten Years (1993 to 2003) of the Gadchiroli Field Trial: Effect of Home-Based Neonatal Care

Abstract: The HBNC package in the Gadchiroli field trial reduced the neonatal and perinatal mortality by large margins, and the gains were sustained at the end of the 7 years of intervention and were carried forward as improved survival through the first year of life. Most of the reduction in mortality was ascribed to sickness management, that is, management of sepsis, supportive care of LBW neonates and management of asphyxia, in that order, and a small portion to primary prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
155
0
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 191 publications
(164 citation statements)
references
References 20 publications
3
155
0
6
Order By: Relevance
“…Seasonal hypothermia rates were not significantly different for LBW compared with normal weight infants in warmer months, but significant differences were found during the colder months. 3 Bang et al 8 reported similar variations from central India (21.5% incidence in the winter versus 13.8% in summer using a definition of hypothermia as <35 1C). In the northern Indian state of Haryana, newborns born at home had an incidence of hypothermia of 19.1% in the winter months, but only 3.1% in the summer.…”
Section: Pathophysiology Of Neonatal Hypothermiamentioning
confidence: 79%
See 3 more Smart Citations
“…Seasonal hypothermia rates were not significantly different for LBW compared with normal weight infants in warmer months, but significant differences were found during the colder months. 3 Bang et al 8 reported similar variations from central India (21.5% incidence in the winter versus 13.8% in summer using a definition of hypothermia as <35 1C). In the northern Indian state of Haryana, newborns born at home had an incidence of hypothermia of 19.1% in the winter months, but only 3.1% in the summer.…”
Section: Pathophysiology Of Neonatal Hypothermiamentioning
confidence: 79%
“…3,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Uniform adoption and application of the standard WHO definition is fundamental to coordinated advancements in detection and management, but hypothermia continues to be variably defined, leading to under-recognition and under-reporting, and inadvertent denial of care to those who are misclassified but in need of care.…”
Section: Definitionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the subsequent article, 24 we have estimated that the homebased interventions in the Gadchiroli trial averted 31 asphyxia related neonatal deaths in 39 villages during 1996 to 2003. (If bag and mask were used from the beginning of intervention, probably more deaths would have been averted.)…”
Section: Discussionmentioning
confidence: 99%